The Struggle of Neural Progenitors in Down Syndrome Brain: The Need for Neuromodulation Beyond Symptomatic Mitigations - Ling, King Hwa; Cheah, Pike See (Malaysian Journal of Medicine and Health Sciences, 2022)
-